Observation of an acoustic octupole topological insulator - Haoran Xue (Nature Portfolio, 2020)
The concept of topological corner states in two dimensional topological insulators can be generalised to higher dimensions. Here, authors present a three dimensional acoustic metamaterial that exhibits the full hierarchy of topological multipole states including corner, hinge, surface and bulk states.